2017
DOI: 10.1007/978-981-10-3773-3_64
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Acute Leukemia Using K-mean Clustering Algorithm

Abstract: Leukemia is a hematologic cancer which develops in blood tissue and triggers rapid production of immature and abnormal shaped white blood cells. Based on statistics it is found that the leukemia is one of the leading causes of death in men and women alike. Microscopic examination of blood sample or bone marrow smear is the most effective technique for diagnosis of leukemia. Pathologists analyze microscopic samples to make diagnostic assessments on the basis of characteristic cell features. Recently, computeriz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The proposed work is evaluated repetitively on a large number of images. To reduce the computational time of GLCM, the number of gray levels of the image is reduced from 256 to 32 levels by dividing the resized image (12) with an appropriate value [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed work is evaluated repetitively on a large number of images. To reduce the computational time of GLCM, the number of gray levels of the image is reduced from 256 to 32 levels by dividing the resized image (12) with an appropriate value [19].…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Sachin Kumar et al [12] demonstrated a method of segmentation by k-means clustering with the assistance of color, texture, geometrical and shape features of the nucleus. They used KNN and Naïve Bayes classifiers to achieve effective classification with the accuracy rate of 92.8%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments on a dataset of 1030 blood smear WBC images produced an average accuracy of 98.6% for this framework. Kumar et al [13] presented an automated detection system for acute leukemia. The system started with the pre-processing of noise and blurring in microscopic digital images.…”
Section: Traditional Methodsmentioning
confidence: 99%
“…In 2018, Kumar et al proposed a new scheme for the detection of leukaemia cells by first applying morphological cleaning to enhance the tested image of the blood. The colour k‐mean clustering is then applied to the L * a * b colour space of the blood image to segment the WBCs from the tested microscopic image [16]. In addition, the bounding box technique is applied on the ( a *) component of the L * a * b colour space to crop blast cells from the microscopic blood images.…”
Section: Literature Reviewmentioning
confidence: 99%